HUMAN RESOURCES DEVELOPMENT STRATEGY IN IMPROVING SERVICE EXCELLENT AT STATE ISLAMIC COLLEGE IN ACEH - Mukhsinuddin, Mukhsinuddin; Saputra, Fedry; Khatami, M; Tullah, Harir Rizky (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Islamic religious colleges are educational institutions that are currently becoming options for prospective students who want to pursue higher education. To become the main choice for prospective new students, PTKIN must certainly improve the quality of its educational institutions. One of the highlights is the Human Resources (HR) section of PTKIN. To achieve this level, PTKIN must improve service excellence in its institutions; therefore, we are interested in researching the Human Resources Development Strategy for improving service excellence at State Islamic Religious Colleges in Aceh. This study uses a qualitative method with a descriptive analysis model; this study was conducted at 5 PTKIN in Aceh (STAIN Teugku Dirundeng, UIN Ar-Raniry, IAIN Lhokseumawe, IAIN Langsa, and IAIN Takengon). The results of the HRM Strategy affect the service performance of PTKIN organizations in Aceh Province. This means that the better the self-ability of the HRD strategy is, the more it will improve the service performance of PTKIN organizations in Aceh Province. HRD's capabilities in good management strategies directly affect the performance of PTKIN organizations in Aceh Province. Employee performance with excellent service will directly affect the performance of PTKIN organizations in Aceh Province. This means that the better the employee performance, the more it will improve the performance of PTKIN organizations in Aceh Province.